Aspek Linguistik Dan Non Linguistik Yang Mempengaruhi Siswa Dalam Pembelajaran Bahasa Arab Di SMP Alfa Ali Masykur - Khoeru Zaqiyah; Shabrina Khalina; Dewi Anggraini; Fatih Alifah; Farah faida (SPESIFIK: Jurnal Pendidikan dan Pembelajaran, 2024)
Learning Arabic cannot be separated from linguistic and non-linguistic aspects. Linguistic aspects, for example related to vocabulary, Arabic grammar (nahwu and sharaf), language skills (speaking skills, listening skills, reading skills and writing skills) and non-linguistic aspects include teachers, student motivation, learning process and learning environment. This research aims to explore the influence of these two aspects in learning Arabic at Alfa Ali Maskur Middle School, Mojotengah, Wonosobo. This research is qualitative descriptive research in the form of field research with data collection methods in the form of observations which function to determine all Arabic language learning activities and interviews as reinforcement for obtaining data related to the influence of linguistic and non-linguistic aspects that influence it. The data analyst uses data triangulation and inductive thinking. The results of this research illustrate that in learning Arabic at Alfa Ali Maskur Middle School, non-linguistic aspects really help improve the linguistic aspects of students whose backgrounds have never studied Arabic at a previous level of education, especially in the aspect of increasing motivation for learning Arabic. This indicates that students' lack of proficiency regarding Arabic language skills and its elements can be improved properly when the learning system is created and prepared well and implemented appropriately while always paying attention to linguistic and non-linguistic aspects.